Influence of the addition of grapes pomace during single or double batch distillation on the chemical composition of wine distillates - Mitev Panko; Ginev Miroslav; Stoyanov Nikolay (BIO Web of Conferences)
The purpose of the research is to determine the influence of the addition of grapes pomace during single or double batch distillation on the chemical composition of wine distillates. The change in the content of aldehydes, esters, higher alcohols and methanol in the three distillate fractions during a single batch distillation with the presence of 10% of pomace, as well as with the addition of that pomace at a different stage of the distillations during double batch distillation, was established. In order to trace the influence of the presence of pomace during distillation on the aromatic profile of the distillates, the change in the chemical compounds trans linalool oxide, nerol, cis linalool oxide, alpha terpeneol, beta citronellol, beta damascone in the three distillate fractions was established.